P2‐Quinazolinones and Bis‐Macrocycles as New Templates for Next‐Generation Hepatitis C Virus NS3/4a Protease Inhibitors: Discovery of MK‐2748 and MK‐6325. Issue 4 (10th March 2015) - Rudd, Michael T.; Butcher, John W.; Nguyen, Kevin T.; McIntyre, Charles J.; Romano, Joseph J.; Gilbert, Kevin F.; Bush, Kimberly J.; Liverton, Nigel J.; Holloway, M. Katharine; Harper, Steven; Ferrara, Marco; DiFilippo, Marcello; et al.
Abstract: With the goal of identifying inhibitors of hepatitis C virus (HCV) NS3/4a protease that are potent against a wide range of genotypes and clinically relevant mutant viruses, several subseries of macrocycles were investigated based on observations made during the discovery of MK‐5172. Quinazolinone‐containing macrocycles were identified as promising leads, and optimization for superior cross‐genotype and mutant enzyme potency as well as rat liver and plasma concentrations following oral dosing, led to the development of MK‐2748. Additional investigation of a series of bis‐macrocycles containing a fused 18‐ and 15‐membered ring system were also optimized for the same properties, leading to the discovery of MK‐6325. Both compounds display the broad genotype and mutant potency necessary for clinical development as next‐generation HCV NS3/4a protease inhibitors. Abstract : Breakthrough antivirals: We describe the discovery of two hepatitis C virus (HCV) NS3/4a protease inhibitors with excellent potency against a broad genotype and mutant range. It is anticipated that such wide‐scope activity will be a prerequisite for successful clinical development of next‐generation antiviral agents.